Publication Trends in Physics Education: A Bibliometric study - Jamali, S.M. (University of Malaya, 2015)
A publication trend in Physics Education by employing bibliometric analysis leads the researchers to describe current scientific movement. This paper tries to answer “What do Physics education scientists concentrate in their publications?” by analyzing the productivity and development of publications on the subject category of Physics Education in the period 1980–2013. The Web of Science databases in the research areas of “EDUCATION - EDUCATIONAL RESEARCH” was used to extract the publication trends. The study involves 1360 publications, including 840 articles, 503 proceedings paper, 22 reviews, 7 editorial material, 6 Book review, and one Biographical item. Number of publications with “Physical Education” in topic increased from 0.14 % (n = 2) in 1980 to 16.54 % (n = 225) in 2011. Total number of receiving citations is 8071, with approximately citations per papers of 5.93. The results show the publication and citations in Physic Education has increased dramatically while the Malaysian share is well ranked.